Review of the Implementation of Stunting Prevention Policy in Galang District, Deli Serdang Regency - Suarni, Suarni; Batubara, Beby Masitho; Lubis, Maksum Syahri (Journal La Sociale, 2025)
Stunting prevention is one of the important strategic efforts in improving the quality of public health, especially in children under five years old. This study aims to evaluate the implementation of stunting prevention policies in Galang District, Deli Serdang Regency, as well as identify factors that hinder the effectiveness of the program. The method used is qualitative research with a case study approach, involving in-depth interviews with local governments, health workers, and local communities. The results of the study show that the stunting prevention programs implemented, such as supplementary feeding (PMT), child growth monitoring, and nutrition education, have had a positive impact on increasing public awareness of the importance of child nutrition. However, there are still obstacles in the implementation of this program, including low community participation, limited health workers, and inadequate socio-economic and sanitation problems. The main inhibiting factors include low public awareness, limited health facilities, and difficult economic conditions, which limit access to nutritious food and health services. Therefore, it is recommended to strengthen public education, improve training for health workers, and improve sanitation infrastructure and access to clean water to support the success of stunting prevention policies more effectively.